Effect of TPS strategy in teaching basketball defensive skills in female students of Physical Education and Sports Sciences - Thajeel, Emad K; Yousef, Rashad T (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of the present study was to recognize the effect of the TPS strategy in teaching defensive skills in basketball for female students. The research community was identified, represented by the second-level students of the faculty of Physical Education and Sports Sciences of Dhi Qar University. In this study, participants were allocated into two groups, experimental group and control group, with n=16 participants in each group. Control group participants were given training with basic curriculum and experimental group participants were given educational training based on the TPS (Think - Pair - Share) strategy. The findings of the present study revealed significant improvement in the defensive skills of the participants of the experimental group.